2005
DOI: 10.1007/s11661-005-0056-9
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Ni-Co alloys with tailorable grain size and twin density

Abstract: We present an experimental approach to systematically produce nanostructures with various grain sizes and twin densities in the Ni-Co binary system. Using electrodeposition with various applied current densities and organic additive contents in the deposition bath, we synthesize nanostructured fcc and hcp solid solutions with a range of compositions. Due to the low stacking fault energy (SFE) of these alloys, growth twins are readily formed during deposition, and by adjusting the deposition conditions, a range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 62 publications
(88 reference statements)
3
27
0
Order By: Relevance
“…4b. Similar pyramidal morphology was also observed for Co-rich Ni-Co films in earlier study [24]. Consequently, the surface morphology of the electrodeposited Ni-Co thin films gradually changes from a structure with roundedshaped grains into a structure with pyramidal-shaped grains and also the grain size increases as the Co ion concentration within the electrolyte increases, consequently the Co content within the films as summarized in Table 1.…”
Section: Resultssupporting
confidence: 83%
“…4b. Similar pyramidal morphology was also observed for Co-rich Ni-Co films in earlier study [24]. Consequently, the surface morphology of the electrodeposited Ni-Co thin films gradually changes from a structure with roundedshaped grains into a structure with pyramidal-shaped grains and also the grain size increases as the Co ion concentration within the electrolyte increases, consequently the Co content within the films as summarized in Table 1.…”
Section: Resultssupporting
confidence: 83%
“…The grain size gradually Effect of Annealing on Mechanical Properties and Nanoscale Lamellar Structure in Co-Cu Alloyincreased with annealing temperature up to 773 K, and then it rapidly increased from 773 to 873 K. This trend was independent of the addition of saccharin. Wu et al 26) showed that grain refinement was enhanced for Ni-Co alloy by the addition of saccharin. In the present work, however, the addition of saccharin addition did not necessarily induce grain refinement of the Co-Cu alloy.…”
Section: Resultsmentioning
confidence: 99%
“…[34][35][36][37][38][39] The deposition parameters, such as solution composition, current density, and bath movement, strongly influence the developing microstructure. The exact mechanisms of microstructure formation are still largely unknown, in part because a precise characterization of the microstructure has rarely been undertaken.…”
Section: B ''Nanocrystalline'' Nico Depositsmentioning
confidence: 99%